Multi-Disciplinary Survey of the Sénégal/Gambia Continental Margin - Ruffman, A.; Meagher, L.; Stewart, J. McG.; Monahan, D. (The International Hydrographic Review, 2015)
The hydrographic results of a major Canadian Hydrographic Service and Atlantic Geoscience Centre multi-disciplinary survey using CSS Baffin off Sénégal and The Gambia are presented. A compiled bathymetry map of the shelf and continental margin of Sénégal and The Gambia has been produced for the area from 11° N to 18" N and 15.5° W to 22.5" W. The continental shelf north of Dakar is relatively narrow and is highly incised by active canyons that pass across the continental slope and rise to feed two channel systems that drain south to the Gambia Abyssal Plain. Immediately south of the Cayar Canyon, which has incised the shelf almost to the shoreline, there appears to be a lack of active canyons, and there are only two canyons west and southwest of Dakar ; both are probably inactive features that ceased to operate when the Cayar Canyon captured their sediment supply. The Cayar and Mauritania/Nouakchott Canyon systems flow into the Cayar and Mauritania deepocean channel systems respectively and both drain south onto the Gambia Abyssal Plain. Various seamounts are mapped offshore. Slumping is mapped on the continental slope including the major Cayar Slide complex which has moved from north of Cayar Seamount and flowed west over 400 km to collide with the Bafoulabé Rise. The density and possibly the initiation of canyons along the shelf edge and slope is believed to be related to the amount of slumping. Additional salt domes are mapped off the Casamance. Minor variations in depth on the shelf are caused by salt dome intrusion, exposed volcanic rocks, sediment piled into ridges by longshore drift or wave conditions and by relict beaches. Aeolian-laid sediment deposition may be responsible for flattening of the shelf and prograding of the shoreline just north of Sénégal off southern Mauritania.